2021
DOI: 10.1002/srin.202100347
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rare‐Earth La on Inclusion Evolution in High‐Al Steel

Abstract: To investigate the evolution of inclusions in high‐Al steel with addition of La, a series of laboratory experiments and thermodynamic calculations are performed, considering the reaction time and amount of La added. The main inclusions in the high‐Al steel without the addition of La are Al2O3, MnS, and Al2O3–MnS. The La treatment can efficiently modify Al2O3 to La–Al–O or La–O–S inclusions. For La additions less than 0.0041 wt%, the evolution route for the inclusion in high‐Al steel is Al2O3 → LaAl11O18 → LaAl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 39 publications
0
39
0
Order By: Relevance
“…Li et al [34] reported that adding Ce could transform Al-Ca-Si-O inclusions into Ce 2 O 2 S and Ce 2 O 3 . Li [35] and Gong et al [36] demonstrated that La could modify the inclusions in steel to La-Al-O, La-O-S, La-S, and other La-containing inclusions. It was clear that the individual addition of Ce or La to steel would form Ce-containing or La-containing inclusions, respectively.…”
Section: Thermodynamic Calculation Of Rare Earth Inclusion Formationmentioning
confidence: 99%
“…Li et al [34] reported that adding Ce could transform Al-Ca-Si-O inclusions into Ce 2 O 2 S and Ce 2 O 3 . Li [35] and Gong et al [36] demonstrated that La could modify the inclusions in steel to La-Al-O, La-O-S, La-S, and other La-containing inclusions. It was clear that the individual addition of Ce or La to steel would form Ce-containing or La-containing inclusions, respectively.…”
Section: Thermodynamic Calculation Of Rare Earth Inclusion Formationmentioning
confidence: 99%
“…[23][24][25][26][27][28][29] To date, however, no systematic summary of research on the physical metallurgy of Te in special steels has been presented. Additionally, in the field of inclusion modification, calcium, [30][31][32] magnesium, [33] rare earth, [34][35][36] and composite treatments [37][38][39] are commonly applied. These treatments have also been applied to the S-bearing NQTS in laboratory experiments.…”
Section: Doi: 101002/srin202200375mentioning
confidence: 99%
“…[4] Al 2 O 3 and AlN inclusions are hard and brittle and can deteriorate the properties of steel. [5][6][7] Li et al [8] previously reported a method for controlling Al 2 O 3 formation by adding rare-earth La to high-Al steel; however, the formation of AlN inclusions remained a significant problem, and excess La even promoted AlN formation. Based on the combination ability of Ti and N, we added Ti to TRIP steel to control the formation of AlN inclusion in the present study.…”
Section: Introductionmentioning
confidence: 99%